Conference on Librarians for the Cyber World 2015 - PPM, Persatuan Pustakawan Malaysia (2015)
Celebrating Librarians Association of Malaysia (Persatuan Pustakawan Malaysia) diamond jubilee (1955 - 2015) 60 years of leadership and commitment towards librarianship in Malaysia